(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
The fallopian tubes convey the ova from the ovaries, transmit spermatozoa and provides the appropriate environment for fertilization and transports the developing embryo to the uterus. Tubal pregnancy, tuberculosis, inflammation, tumor are the common pathology of the fallopian tubes. Complete or partial bilateral tubal block or adhesions may develop from clinical conditions which lead to infertility. Appropriate histomorphological knowledge about the fallopian tube is essential for proper diagnosis and management of tubal diseases and infertility cases. This is a cross sectional, descriptive type of study which was carried out in the Department of Anatomy, Sir Salimullah Medical College (SSMC), Dhaka from Jan 2011 to Dec 2011. The number of sample was sixty two pairs of cadaveric human fallopian tubes which were collected from unclaimed dead bodies of the morgue of Dhaka Medical college. Among the studied samples, the lowest age was 2 years and the highest age was 65 years. The samples were divided into four different age groups. They were group A or prepubertal group (2-12years), group B or reproductive group (13-45 years), group C or perimenopausal group (46-51years) and post menopausal group (52-65 years). Histomorphological studies were carried out on 24 relatively fresh samples, 6 samples from each group. There was statistically significant difference found when values were compared between different age groups and also not significant between different age group. This study has revealed an age related change in wall thickness of fallopian tube. J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 43-48